2021
DOI: 10.3390/jcm10081702
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on the Development of Dental Caries in Children. A Radiographic Study

Abstract: Dental caries is a chronic disease that can be influenced by a multitude of factors. Poor oral hygiene and unhealthy eating habits are the most incriminating factors in the onset of dental caries, but age has been proven to impact the disease. The aim of this study was to find correlations between age and the evolution of dental caries in the first permanent molars in children. The retrospective study was conducted based on 400 panoramic radiographs, belonging to Romanian children between the ages of 6 and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This is in line with several studies that have reported an increased incidence of caries in first permanent molars [36,37]. Contrary to our findings, there are authors who reported a higher incidence of caries in the upper arch than in the lower arch [38], but our results are consistent with the results obtained in a previously published radiographic study in which first permanent molars were investigated, and in which superficial, medium, or deep caries prevailed in the lower arch [39].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with several studies that have reported an increased incidence of caries in first permanent molars [36,37]. Contrary to our findings, there are authors who reported a higher incidence of caries in the upper arch than in the lower arch [38], but our results are consistent with the results obtained in a previously published radiographic study in which first permanent molars were investigated, and in which superficial, medium, or deep caries prevailed in the lower arch [39].…”
Section: Discussionsupporting
confidence: 93%
“…The extraction of P1Ms in various clinical situations should be considered with the poor prognosis of P1M. Extraction is advised at a suitable time to minimize the negative effects on occlusion in severely compromised/carious P1Ms with endodontic treatment needs, failed endodontic treatment and hypoplasia [1].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has conflicting views on P1Ms extraction. Some report that P1M extraction can dysfunction the masticatory system and maxillofacial tissues including skeletal, dental and periodontal tissues [1][2][3]. A missing tooth can have undesired outcomes such as gaps, tipping and/or rotation, and/or mesial-distal drifting, and/or lingual tilting of neighboring teeth, incisors retrusion and need for orthodontic treatment after the extraction [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it tends to have deeper pits and fissures that trap food, resulting in dental caries and tooth loss. 3 4…”
Section: Introductionmentioning
confidence: 99%